Phosphoproteomic identification of vasopressin‐regulated protein kinases in collecting duct cells. (14th February 2021) - Datta, Arnab; Yang, Chin‐Rang; Salhadar, Karim; Park, Euijung; Chou, Chung‐Lin; Raghuram, Viswanathan; Knepper, Mark A.
Abstract : Background and Purpose: The peptide hormone vasopressin regulates water transport in the renal collecting duct largely via the V2 receptor, which triggers a cAMP‐mediated activation of a PKA‐dependent signalling network. The protein kinases downstream from PKA have not been fully identified or mapped to regulated phosphoproteins. Experimental Approach: We carried out systems‐level analysis of large‐scale phosphoproteomic data quantifying vasopressin‐induced changes in phosphorylation in aquaporin‐2‐expressing cultured collecting duct (mpkCCD) cells. Quantification was done using stable isotope labelling (SILAC method). Key Results: Nine thousand six hundred forty phosphopeptides were quantified. Stringent statistical analysis identified significant changes in response to vasopressin in 429 of these phosphopeptides. The corresponding phosphoproteins were mapped to known vasopressin‐regulated cellular processes. The vasopressin‐regulated sites were classified according to the sequences surrounding the phosphorylated amino acids giving 11 groups. Among the vasopressin‐regulated phosphoproteins were 25 distinct protein kinases. Among these, six plus PKA appeared to account for phosphorylation of about 81% of the 313 vasopressin‐regulated phosphorylation sites. The six downstream kinases were salt‐inducible kinase 2 (Sik2), cyclin‐dependent kinase 18 (Cdk18), calmodulin‐dependent kinase kinase 2 (Camkk2), protein kinase D2 (Prkd2), mitogen‐activated kinase 3 (Mapk3) and myosin light chain kinase (Mylk). Conclusion and Implications: In V2 receptor‐mediated signalling, PKA is at the head of a complex network that includes at least six downstream vasopressin‐regulated protein kinases that are prime targets for future study. The extensive phosphoproteomic data reported in this study are provided as a web‐based data resource for future studies of GPCRs. [Correction added on 4 March 2021, after first online publication: The first sentence in the Key Results was corrected in this current version.]